Control of butters in lines culinaris medic - V. Reznik; S. Moshkovska (Карантин і захист рослин)
Goal. To develop an effective system for the protection of crops of lentils from weeds by chemical methods. Objective: to investigate the dynamics of the processes of weed infestation, the species composition of weeds, the structure, number and mass of weeds; to study the factors of the negative impact of weeds on lentil plants in the process of their joint vegetation; search and evaluation in field conditions of the effectiveness of herbicides and their compositions on edible lentil crops.